Hybrid Window and Rate Based Congestion Control for Delay Sensitive Applications - Mehrotra, Sanjeev; Li, Jin; Sengupta, Sudipta; Jain, Manish; Sen, Sayandeep (Proceedings Globecom 2010, 2010)
There has been a dramatic increase in interactive cloud based software applications. Compared to classical realtime media applications (voice over IP (VoIP)/conferencing) and non real-time ﬁle delivery, these interactive software applications have unique characteristics: 1) they are delay sensitive yet demand in order and reliable data delivery, and 2) the trafﬁc is usually bursty. Traditional window based congestion control does not work well for interactive applications because the bursty arrival of data leads to bursty network trafﬁc, which causes additional queuing delay and packet loss in the network which reduces its delay performance. In this paper, we propose a new hybrid window plus rate based congestion control technique. This algorithm improves the delay performance of interactive applications by preventing congestion induced loss and minimizing queuing delay while still fully utilizing network capacity and maintaining fairness across multiple ﬂows.